Implementation of inventory management techniques to optimize a spare parts warehouse in a chemical industry located in the municipality of Ortigueira - PR - Fuglini, Maria Elisa Ximarelli; Budeiz, Geovana Bellato de Malta; dos Santos Filho, Vitor Hugo (Brazilian Journal of Production Engineering, 2024)
This study aimed to implement inventory management techniques in order to optimize the spare parts warehouse of a chemical industry located in the municipality of Ortigueira - PR. As a methodology, a physical inventory of the company's critical materials was carried out, evaluating the accuracy by implementing the ABC curve method and a continuous review model of materials, determining from the variables, some indicators, such as: Lead Time, average demand, service level, standard deviation and safety stocks for each Stock Keep Unit (SKU). After applying the inventory, there was a divergence of 16% between system and physical, having a high-cost impact for the company, since, after the ABC classification of the materials, it was verified that the materials classified as A, represented 64% in monetary value for the warehouse. Therefore, the safety stock was defined for the 125 inventoried SKUs, obtaining different stocks, due to the Lead Time and average demand being different for the materials. With this, the study presents a new model of inventory management, based on techniques capable of reducing costs for the company.
Keywords: Inventory Management; Continuous Review Model; ABC Classification; Safety Stock